Implementasi Media Animasi Interaktif Berbasis Etnomatematika untuk Meningkatkan Literasi Statistika Siswa - M. Asfar Abdul Majid; Ernawati (CV. Insight Publisher, 2025)
The low level of students’ statistical literacy remains a challenge in mathematics education in Indonesia, partly due to conventional and non-contextual teaching approaches. This study aims to evaluate the effectiveness of ethnomathematics-based interactive animation media in improving the statistical literacy of junior high school students. A quantitative method with a pretest–posttest design was applied to two groups: the experimental group used the interactive animation media, while the control group received conventional instruction. The instrument used was a statistical literacy test covering the ability to read, interpret, and draw conclusions from data within a local cultural context. The results showed a significant increase in posttest scores in both groups, with higher gains in the experimental group. An independent sample t-test revealed a significant difference between the two groups (p = 0.001), indicating the effectiveness of the ethnomathematics-based media. These findings suggest that integrating digital media with local culture enhances learning outcomes and creates more meaningful, contextual learning experiences. The study recommends the development of similar media across other subjects to strengthen culture-based literacy.